Associations of dairy product consumption with mortality in the European Prospective Investigation into Cancer and Nutrition (EPIC)–Italy cohort. Issue 5 (21st August 2019) - Pala, Valeria; Sieri, Sabina; Chiodini, Paolo; Masala, Giovanna; Palli, Domenico; Mattiello, Amalia; Panico, Salvatore; Tumino, Rosario; Frasca, Graziella; Fasanelli, Francesca; Ricceri, Fulvio; Agnoli, Claudia; et al.
ABSTRACT: Background: The relation of dairy product consumption to health and mortality is controversial. Objectives: We investigated associations of consumption of various dairy products with mortality in the Italian cohort of the European Prospective Investigation into Cancer and Nutrition (EPIC)–Italy study. Methods: Dairy product consumption was assessed by validated semiquantitative FFQs. Multivariable Cox models stratified by center, age, and sex and adjusted for confounders estimated associations of milk (total, full fat, and reduced fat), yogurt, cheese, butter, and dairy calcium consumption with mortality for cancer, cardiovascular disease, and all causes. Nonlinearity was tested by restricted cubic spline regression. Results: After a median follow-up of 14.9 y, 2468 deaths were identified in 45, 009 participants: 59% from cancer and 19% from cardiovascular disease. No significant association of consumption of any dairy product with mortality was found in the fully adjusted models. A 25% reduction in risk of all-cause mortality was found for milk intake from 160 to 120 g/d (HR: 0.75; 95% CI: 0.61, 0.91) but not for the highest (>200 g/d) category of intake (HR: 0.95; 95% CI: 0.84, 1.08) compared with nonconsumption. Associations of full-fat and reduced-fat milk consumption with all-cause and cause-specific mortality were similar to those for milk as a whole. Conclusions: In this Italian cohort characterized by low to average milk consumption, we found no evidence of a dose–response association between milk consumption and mortality and also no association of consumption of other dairy products investigated with mortality.